The design of quantum dots and their conjugates as luminescent probes for analyte sensing - Adegoke, Oluwasesan (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
The design and applications of quantum dots (QDs) as fluorescent probes for analyte sensing is presented. Cadmium based thiol-capped QDs were employed as probe for the detection of analytes. Comparative studies between core CdTe and core-shell CdTe@ZnS QDs showed that the overall sensitivity and selectivity of the sensor was dependent on the nature of the capping agent and the QDs employed, hence making CdTe@ZnS QDs a more superior sensor than the core. To explore the luminescent sensing of QDs based on the fluorescence "turn ON" mode, L-glutathione-capped CdTe QDs was conjugated to 4-amino-2,2,6,6-tetramethylpiperidine-N-oxide (4AT) to form a QDs-4AT conjugate system. The QDs-4AT nanoprobe was highly selective and sensitive to the detection of bromide ion with a very low limit of detection. Subsequently, metallo-phthalocyanines (MPcs) were employed as host molecules on the surface of QDs based on the covalent linking of the QDs to the MPc. Elucidation of the reaction mechanism showed that the fluorescence "turn ON" effect of the QDs-MPc probe in the presence of the analyte was due to axial ligation of the analytes to the Pc ring. Studies showed that the type of substituent attached to the MPc ring influenced the overall sensitivity of the probe. Additionally, a comparative investigation using newly synthesized phthalocyanine and triaza-benzcorrole complexes was conducted when these complexes were conjugated to CdSe@ZnS QDs for analyte sensing. Results showed that the triaza-benzcorrole complex can be employed as a host-molecule sensor but displayed a lower sensitivity for analyte sensing in comparison to the phthalocyanine complex.
Keywords: Quantum dots; Anolytes; Luminescent probes; Luminescence spectroscopy; Phthalocyanines; Nanoparticles